Gastroesophageal reflux disease in children - N. S. Zhikharyoeva (Медицинский совет, 2013)
According to the WHO classification, gastroesophageal reflux disease is a chronic relapsing disease caused by violation of motor-evacuation function of the gastroesophageal zone characterized by spontaneous or regular backflow of gastric or duodenal contents into the esophagus resulting in damage of distal esophagus. Gastroesophageal reflux disease develops regardless of whether there are any or no morphological changes in the esophagus.